Recombinant " IMS TAG" proteins – A new method for validating bottom‐up matrix‐assisted laser desorption/ionisation ion mobility separation mass spectrometry imaging. (1st October 2013) - Cole, Laura M.; Mahmoud, Khaled; Haywood‐Small, Sarah; Tozer, Gillian M.; Smith, David P.; Clench, Malcolm R.
Abstract : RATIONALE: Matrix‐assisted laser desorption/ionisation mass spectrometry imaging (MALDI‐MSI) provides a methodology to map the distribution of peptides generated by in situ tryptic digestion of biological tissue. It is challenging to correlate these peptides to the proteins from which they arise because of the many potentially overlapping and hence interfering peptide signals generated. METHODS: A recombinant protein has been synthesised that when cleaved with trypsin yields a range of peptide standards for use as identification and quantification markers for multiple proteins in one MALDI‐IMS‐MSI experiment. Mass spectrometry images of the distribution of proteins in fresh frozen and formalin‐fixed paraffin‐embedded tissue samples following in situ tryptic digestion were generated by isolating signals on the basis of their m/z value and ion mobility drift time, which were correlated to matching peptides in the recombinant standard. RESULTS: Tryptic digestion of the IMS‐TAG protein and MALDI‐MS analysis yielded m/z values and ion mobility drift time for the signature peptides included in it. MALDI‐IMS‐MSI images for the distribution of the proteins HSP90 and vimentin, in FFPE EMT6 mouse tumours, and HSP90 and plectin in a fresh frozen mouse fibrosarcoma, were generated by extracting ion images at the corresponding m/z value and drift time from the tissue samples. CONCLUSIONS: The IMS‐TAG approach provides a new means to confirm the identity of peptides generated by in situ digestion of biological tissue. Copyright © 2013 John Wiley & Sons, Ltd.